Expanding the Safety Net of Specialty Care for the Uninsured: A Case Study - Spatz, Erica S (Blackwell Science Inc, 2012)
OBJECTIVE: To describe core principles and processes in the implementation of a navigated care program to improve specialty care access for the uninsured. STUDY SETTING: Academic researchers, safety-net providers, and specialty physicians, partnered with hospitals and advocates for the underserved to establish Project Access-New Haven (PA-NH). PA-NH expands access to specialty care for the uninsured and coordinates care through patient navigation. STUDY DESIGN: Case study to describe elements of implementation that may be relevant for other communities seeking to improve access for vulnerable populations. PRINCIPAL FINDINGS: Implementation relied on the application of core principles from community-based participatory research (CBPR). Effective partnerships were achieved by involving all stakeholders and by addressing barriers in each phase of development, including (1) assessment of the problem; (2) development of goals; (3) engagement of key stakeholders; (4) establishment of the research agenda; and (5) dissemination of research findings. CONCLUSIONS: Including safety-net providers, specialty physicians, hospitals, and community stakeholders in all steps of development allowed us to respond to potential barriers and implement a navigated care model for the uninsured. This process, whereby we integrated principles from CBPR, may be relevant for future capacity-building efforts to accommodate the specialty care needs of other vulnerable populations.